2008
DOI: 10.1038/sj.bjc.6604221
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation with ‘naïve’ syngeneic dendritic cells protects mice from tumour challenge

Abstract: Dendritic cells (DCs) 'pulsed' with an appropriate antigen may elicit an antitumour immune response in mouse models. However, while attempting to develop a DC immunotherapy protocol for the treatment of breast cancer based on the tumour-associated MUC1 glycoforms, we found that unpulsed DCs can affect tumour growth. Protection from RMA-MUC1 tumour challenge was achieved in C57Bl/6 MUC1 transgenic mice by immunising with syngeneic DCs pulsed with a MUC1 peptide. However, unpulsed DCs gave a similar level of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We and others have demonstrated that vaccination with DCs result in NK cell-mediated tumor regression in several tumor transplant models (14,(16)(17)(18)(19) and now in a new peritoneal tumor model (data not shown). We next tested whether NK cells activated in this way could prevent the de novo generation of chemically induced tumors.…”
Section: Prevention Of Mca-induced Sarcoma Formation In Dc-immunized mentioning
confidence: 83%
“…We and others have demonstrated that vaccination with DCs result in NK cell-mediated tumor regression in several tumor transplant models (14,(16)(17)(18)(19) and now in a new peritoneal tumor model (data not shown). We next tested whether NK cells activated in this way could prevent the de novo generation of chemically induced tumors.…”
Section: Prevention Of Mca-induced Sarcoma Formation In Dc-immunized mentioning
confidence: 83%